The impact of digital transformation on creative accounting practices - Berrehouma, narimane; Habi, ahmed (Journal of Research in Finance and Accounting, 2023)
This study aimed to identify the terms "digital transformation" and "creative accounting", and to identify the benefits and challenges of applying digital transformation techniques in the field of accounting. It also highlighted the relationship between digital transformation and creative accounting and its impact on the course of creative accounting practices. To achieve the objectives of the study, the descriptive approach was preferred. The study concluded that digital transformation through its techniques redefines the concept of creative accounting, in the context in which the digital body and intangible technology can positively influence accounting, reporting and taxation of real activities in the economy. It also enhances the scope of positive creative accounting practices by linking them to markets and rapidly evolving payment systems.